Governance of Retail Payment Systems : Keeping Pace with Changing Markets - World Bank (World Bank, Washington, DC, 2021)
As innovation in retail payments continues and the systems evolve, effective governance of them becomes more complicated and increases in importance. Retail payment systems are essential for the economy to function efficiently, and more and more, they are something on which all individuals rely on in order to participate in economic life. Effective governance arrangements of retail payment systems are critical not just for the stability, reliability, and efficiency of the financial system but also for its capacity to manage and respond to the changing policy and market environment. Governance calls for focused attention, and retail payment systems deserve and require distinct and specific guidance regarding governance. This is because issues related to retail payment system governance go beyond the typical corporate issues, precisely because of the underlying public interest and the broader public policy objectives of safety and efficiency. This paper provides context and considerations regarding the governance of retail payment systems within this changing environment. It provides examples of approaches specific to the governance of retail payment systems and the different factors that influence and guide them. It refers to related legal frameworks, principles, and reference materials that may be useful in conducting reviews. And it draws on and shares examples of the challenges, frameworks, and arrangements of specific countries and systems. The paper provides specific guidance for practical matters, such as the regular assessment and revision of governance arrangements, the importance of acknowledging public interest, maintaining access rules that are in line with market needs and developments, achieving and maintaining a high degree of transparency regarding governance, and in ensuring that the board and management have the right skills and knowledge. The paper concludes with several themes for consideration that will help authorities and other relevant stakeholders navigate the topic of governance for retail payment systems.